The Relationship Between Knowledge Level and Attitudes of the Sanding Gianyar Community Toward the Use of Traditional Medicines for Self-Medication - Fitria Megawati; Ni Putu Dewi Agustini; Luh Santhi Utami Wiryani (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Knowledge is defined as an individual's ability that serves as the basis for decision-making and can influence attitudes. The self-medication process often involves the use of traditional medicine, where its utilization is strongly influenced by the individual's level of knowledge and attitude. Objective: This study aims to determine the relationship between the level of knowledge and community attitudes toward the use of traditional medicine for self-medication in Banjar Dinas Sanding, Gianyar. Methods: This study used a cross-sectional research design with an accidental sampling technique. The sample size was determined using the Slovin formula, resulting in 247 respondents from a population of 649 people who met the inclusion and exclusion criteria. The data used were primary data collected through questionnaires, consisting of a knowledge questionnaire using the Guttman scale and an attitude questionnaire using the Likert scale. Results: Data analysis in this study was conducted using univariate and bivariate analyses. The results showed that in the knowledge aspect, 153 respondents (61.94%) had good knowledge, while 94 respondents (38.06%) had poor knowledge. In the attitude aspect, 152 respondents (61.55%) showed a positive attitude, while 95 respondents (38.46%) had a negative attitude. The analysis of the influence of knowledge level on community attitudes was performed using SPSS with the Chi-Square test, which produced a p-value of 0.001 (p < 0.05).Conclusion: There was a significant relationship between the level of knowledge and attitudes toward the use of traditional medicine in Banjar Dinas Sanding, Gianyar.